2018
DOI: 10.24940/ijird/2018/v7/i9/sep18014
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Work: An Educational Program for Improving Nurses` Productivity

Abstract: Introduction Recently, with changing and expanded working settings, nurses repetitively act in unanticipated circumstances in different settings as a serious part of the healthcare sector to deliver holistic care for patients (Chan, 2013). To handle new and exceptional components in these difficult states, nurses must be ready to reply to any challenges in timely, effective, creative and adaptable ways. Creativity isn't new to the nursing career. Its presentation can be followed back to Myra Levine in 1973 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…The finding of the present study is inconsistent with the result of Abd-Elrhaman and Ghoneimy (2018) (54) found that the majority of staff nurses had low level of creativity as total, (31) stated that nurses had moderate level of creativity in general , and Saleh et al (2013) (55) showed that more than three quarters of staff nurses were below average level of creativity .…”
Section: Kasasbeh Et Al (2014)contrasting
confidence: 99%
See 1 more Smart Citation
“…The finding of the present study is inconsistent with the result of Abd-Elrhaman and Ghoneimy (2018) (54) found that the majority of staff nurses had low level of creativity as total, (31) stated that nurses had moderate level of creativity in general , and Saleh et al (2013) (55) showed that more than three quarters of staff nurses were below average level of creativity .…”
Section: Kasasbeh Et Al (2014)contrasting
confidence: 99%
“…This may be related to high percentage of staff nurses agree about all items of aforementioned elements of staff nurses' creativity. But Abd-Elrhaman and Ghoneimy (2018) (54) found that the majority of staff nurses had low level in all elements of creativity.…”
Section: Tabarestani Et Al (2014)mentioning
confidence: 99%
“…Besides, [ 22 ] revealed that changing and improving nursing management staff's creativity affects their performance at Benha University Hospital. [ 23 ] stated that throughout the program, there was a statistically significant increase in the level of creativity and productivity among staff nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Creativity in different healthcare settings is a complex concept which is result from relational interactions among several essential components and external circumstances in the work environment which can hinder or facilitate employees' creative performance. Organizations should recognize the potential importance of creativity for achievement of employees' performance high levels, which requires a supportive guidance in work environment [8,9] . Nurses' leaders are able to allow the creative process to be evolved in work environment as they can encourage creativity through honest and transparent relations with staff nurses [10,11] .…”
Section: Introductionmentioning
confidence: 99%